(untitled) (Islamic Sciences Journal, 2025)
This study investigates the theological and intellectual legacy of Imam Abū al-Ḥasan al-Ashʿarī, a pivotal figure who emerged after the conclusion of the first three virtuous generations of Islam. His rise coincided with the proliferation of various Islamic sects and doctrinal schools, some of which adopted extreme rationalism in their theological formulations. Imam al-Ashʿarī distinguished himself by his clear and principled defense of the beliefs of Ahl al-Sunnah (Sunni orthodoxy). His extensive knowledge of competing theological factions allowed him to engage in rigorous debates, through which he offered well-informed refutations. Over time, his school of thought—known as the Ashʿarī school—became one of the most influential traditions in Islamic theology, widely embraced by Sunni scholars. The present research centers on a manuscript that highlights the virtues and selected doctrinal perspectives of Imam al-Ashʿarī. Upon discovering the manuscript, I divided it into three distinct studies. This paper constitutes the second part. The manuscript has been critically edited, with authenticated ḥadīths and explanatory footnotes provided for historical figures and theological terms mentioned therein. The study is organized into three main chapters. Chapter One presents the lineage, name origin, birth, and early upbringing of Imam al-Ashʿarī. Chapter Two delves into his theological and intellectual contributions. Chapter Three provides the edited text of the manuscript itself. Through this analysis, the research contributes to a deeper understanding of Imam al-Ashʿarī’s thought and his enduring impact on Islamic theology.